Funding, competition and the efficiency of NGOs: An empirical analysis of noncharitable expenditure of US NGOs engaged in foreign aid - Peter Nunnenkamp; Hannes Öhler (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2010)
We assess the determinants of the wide variation in the efficiency of foreign aid activities across US-based non-governmental organizations (NGOs). In particular, we analyze whether noncharitable expenditures for administration, management and fundraising depend on the intensity of competition among NGOs and on the degree to which they are refinanced by governments. We control for NGO heterogeneity in various dimensions as well as major characteristics of recipient countries. We find that fiercer competition is associated with more efficient foreign aid activities of NGOs, rather than leading to excessive fundraising. Official funding tends to increase administrative costs. Nevertheless, officially financed NGOs spend relatively more on charitable activities since they are less concerned with collecting private donations through fundraising efforts.
Keywords: F35; L31; 330; non-governmental organizations; foreign aid; administrative costs; fundraising; United States; Private Entwicklungshilfe; Wirtschaftliche Effizienz; Verwaltungskosten; Spendensammlung; Wettbewerb; USA